2010
DOI: 10.1097/pep.0b013e3181eab240
|View full text |Cite
|
Sign up to set email alerts
|

Power Mobility and Socialization in Preschool

Abstract: The use and assessment of power mobility in a preschool classroom appear feasible. Issues important to maximizing children's use of power mobility for classroom participation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 20 publications
(8 reference statements)
0
20
0
Order By: Relevance
“…9 In this case report, we continue to follow a 3 year old child, Will, who was the subject of a recent case report focused on the feasibility of using an experimental power mobility device in a preschool classroom. 10 The specific focus of this follow-up report is to determine the feasibility of providing an intervention to increase the use of power mobility for his socialization in the preschool classroom.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In this case report, we continue to follow a 3 year old child, Will, who was the subject of a recent case report focused on the feasibility of using an experimental power mobility device in a preschool classroom. 10 The specific focus of this follow-up report is to determine the feasibility of providing an intervention to increase the use of power mobility for his socialization in the preschool classroom.…”
Section: Introductionmentioning
confidence: 99%
“…First, mobility impairments can limit a child’s ability to initiate and maintain social interactions with their highly mobile peers. 5,10 Second, preschool group activities often require bouts of mobility in tight spaces such as during dramatic play or ‘sensory’ table activities, which are difficult for children with mobility impairments with or without power mobility. 15 Given the tight spaces of a preschool classroom, however, noting how a child spends the majority of his non-interacting time - in parallel play (within 3 feet of another peer) or as solitary (more than 3 feet from others) – may provide more information on the extent to which the child is socially isolated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally important, using this technology results in some of the developmental gains associated with the onset of crawling and walking (Butler et al, 1983;Galloway et al, 2008;Lynch et al, 2009;Livingstone, 2010;Ragonesi et al, 2010;Jones et al, 2012). Unfortunately, the reality is that many if not most of the children who could benefit from powered mobility do not gain access to this technology until after 5 years of age (Nicholson and Bonsall, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Over 30 years of research has demonstrated that young children with disabilities who experience the most severe delays in mobility can use powered mobility devices for self-directed mobility (Butler et al, 1983;Galloway et al, 2008;Lynch et al, 2009;Livingstone, 2010;Ragonesi et al, 2010;Jones et al, 2012). Equally important, using this technology results in some of the developmental gains associated with the onset of crawling and walking (Butler et al, 1983;Galloway et al, 2008;Lynch et al, 2009;Livingstone, 2010;Ragonesi et al, 2010;Jones et al, 2012).…”
Section: Introductionmentioning
confidence: 99%